2022
DOI: 10.1590/2317-1545v44258744
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in physiological potential and biochemical mechanisms of pea seeds under water deficit

Abstract: Nitric oxide (NO) has been standing out as a seed germination process stimulator, mainly under stress conditions. This work aimed to evaluate the physiological and biochemical effects of NO on germination and vigor of pea seeds submitted to water deficit. Seeds of cv. Itapuã 600 were sown in moistened substrate with water (control), PEG 6000 solution (-0.15 MPa) and PEG 6000 solution with sodium nitroprusside (SNP) (-0.15 MPa + 50 μM), an NO donor. The germination, vigor (germination speed and seedling develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…The results obtained in this work showed that water limitation caused by PEG led to a significant increase in H 2 O 2 content in I. walleriana shoots (Figure 7). As in the case of MDA, there are literature data describing the inhibitory effect of SNP on H 2 O 2 production in Malus hupehensis [73], Allium hirtifolium [74], and pea seeds [75]. The results of this work show that all SNP pre-treatments and MDA increased H 2 O 2 content in water deficit-stressed I. walleriana shoots.…”
Section: Discussionsupporting
confidence: 50%
“…The results obtained in this work showed that water limitation caused by PEG led to a significant increase in H 2 O 2 content in I. walleriana shoots (Figure 7). As in the case of MDA, there are literature data describing the inhibitory effect of SNP on H 2 O 2 production in Malus hupehensis [73], Allium hirtifolium [74], and pea seeds [75]. The results of this work show that all SNP pre-treatments and MDA increased H 2 O 2 content in water deficit-stressed I. walleriana shoots.…”
Section: Discussionsupporting
confidence: 50%
“…SNP stands out for being a donor of nitric oxide (NO), an inorganic radical synthesized from L-arginine (Kolbert et al, 2021), which acts in several cellular processes, stimulating germination and breaking dormancy of several species, such as mustard (Rather et al, 2020), tomato (Khan et al, 2021), and pea (Sekita et al, 2022). Similarly, Oliveira et al (2021) observed positive results in the germination of U. brizantha when primed with SNP, showing the positive role of this compound.…”
Section: Resultsmentioning
confidence: 99%